2018
DOI: 10.3389/fmicb.2018.01377
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bacterial Community Composition and Correlation of Environmental Variables in Rambla Salada, a Hypersaline Environment in South-Eastern Spain

Abstract: We studied the bacterial community in Rambla Salada in three different sampling sites and in three different seasons and the effect of salinity, oxygen, and pH. All sites samples had high diversity and richness (Rr > 30). The diversity indexes and the analysis of dendrograms obtained by DGGE fingerprint after applying Pearson's and Dice's coefficient showed a strong influence of sampling season. The Pareto-Lorenz (PL) curves and Fo analysis indicated that the microbial communities were balanced and despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 105 publications
(162 reference statements)
1
16
0
Order By: Relevance
“…Like several other salterns and hypersaline environments, Siridao salterns support diverse communities of phylotypes belonging to Bacteroidetes and Gammaproteobacteria (Sørensen et al, 2005;Baati et al, 2011;Zhang et al, 2016). The occurence of Alphaproteobacteria, Betaproteobacteria and Firmicutes decreased with increasing salinity which was consistent with the results obtained by Oueriaghli et al (2018). A study carried out in the same salterns under investigation, employing DGGE had recovered sequences affiliated with Gammaproteobacteria, supporting their importance at Siridao salterns (Mani et al, 2015).…”
Section: Major Shifts In Bacterial Diversity Between Salt Production supporting
confidence: 83%
See 1 more Smart Citation
“…Like several other salterns and hypersaline environments, Siridao salterns support diverse communities of phylotypes belonging to Bacteroidetes and Gammaproteobacteria (Sørensen et al, 2005;Baati et al, 2011;Zhang et al, 2016). The occurence of Alphaproteobacteria, Betaproteobacteria and Firmicutes decreased with increasing salinity which was consistent with the results obtained by Oueriaghli et al (2018). A study carried out in the same salterns under investigation, employing DGGE had recovered sequences affiliated with Gammaproteobacteria, supporting their importance at Siridao salterns (Mani et al, 2015).…”
Section: Major Shifts In Bacterial Diversity Between Salt Production supporting
confidence: 83%
“…On the other hand, though Spiribacter could tolerate wide salinity fluctuations (0-2 M NaCl), its growth peaks at very specific salinity (0.8 M NaCl) making it difficult to flourish in highly fluctuating salinities ( León et al, 2018 ). Few studies carried out in the salterns of Chile, Argentina, Poland, and Spain have also reported the absence or low incidence of Salinibacter ( Kalwasińska et al, 2018 ; Mora-Ruiz et al, 2018 ; Oueriaghli et al, 2018 ). Further, considering the absence of dominant archaeal phylotype of Haloquadratum and bacterial phylotypes such as Salinibacter and Spiribacter , we are in complete agreement with the views drawn by Gomariz et al (2015) that solar salterns, despite being called ‘steady-state’ systems, undergo various microbial fluctuations at similar salinities and therefore general conclusions should be drawn with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Halophiles thrive in hypersaline niches and have potential applications in biotechnology [1,2]. Microbial diversity in most hypersaline environments is often studied using culture-dependent and -independent methods [3][4][5][6][7]. Previous studies have shown that the taxonomic diversity of microbial populations in terrestrial saline and hypersaline environments is relatively low [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, microbial diversity is high and poorly elucidated by culture techniques, even with different types of culture media, since a large percentage of these microorganisms are nonculturable [7,8]. Therefore, it is necessary to create new research tools that allow the characterization of microbiological biodiversity, i.e., molecular microbial ecology, through the use of high-throughput sequencing technologies with the aid of bioinformatics techniques for data analysis [1,911].…”
Section: Introductionmentioning
confidence: 99%